Images of Antiquity in Moscow Inofficial Art of the Second Half of the 1970s–1980s - Florkovskaia, Anna K. (Actual Problems of Theory and History of Art, 2015)
The emergence of postmodernism in Soviet art dates back to the 1970s and is associated with various phenomena of official and inofficial culture. It is concerned with the names of artists — participants of the painters’ section of the Moscow Municipal Committee of graphic artists (1978–1988): S. Bleze, T. Glytneva, E. Izmailov, K. Kuznetsov, and S. Simakov. Interpreting ancient images they turn their works into so to say multi-layered cultural inter-texts with quotes and comments on classical antiquity and its perceptions in styles and trends of the New Times — baroque, classicism, symbolism, and surrealism. Historiosophy, the synthesis of natural and cultural in landscape painting, irony and manipulation with historical memory, define the inter-textuality of their works. Strategy of inofficial artists is close to mastering the heritage by official art of that time, but differs from the latter due to interpretation and free citation from earlier epochs, “gliding” over the tradition, not “getting into” it. Their greater adherence to antique themes allows us to speak about “Russian antiquity” of the 20th–21st centuries.
Keywords: inofficial art; postmodernism; classical antiquity; tradition; historicism; quote; inter-textuality; mythologism; “Russian antiquity”; natural and cultural landscape